2008
DOI: 10.1002/cne.21619
|View full text |Cite
|
Sign up to set email alerts
|

Deafferentiation‐associated changes in afferent and efferent processes in the guinea pig cochlea and afferent regeneration with chronic intrascalar brain‐derived neurotrophic factor and acidic fibroblast growth factor

Abstract: Deafferentation of the auditory nerve from loss of sensory cells is associated with degeneration of nerve fibers and spiral ganglion neurons (SGN). SGN survival following deafferentation can be enhanced by application of neurotrophic factors (NTF), and NTF can induce the regrowth of SGN peripheral processes. Cochlear prostheses could provide targets for regrowth of afferent peripheral processes, enhancing neural integration of the implant, decreasing stimulation thresholds, and increasing specificity of stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
128
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(140 citation statements)
references
References 57 publications
10
128
1
1
Order By: Relevance
“…However, the effects on soma area associated with neurotrophin administration are much greater than the cell size changes elicited with electrical stimulation. In fact, several previous studies in guinea pigs have shown that 4 weeks of intracochlear infusion of BDNF resulted in large increases in SG perikaryal size compared to deafened cochleae and cross-sectional areas that were even significantly larger than in normal controls (Agterberg et al 2008;Glueckert et al 2008;McGuinness and Shepherd 2005;Shepherd et al 2005Shepherd et al , 2008. The mechanism(s) underlying this alteration are unclear, but we agree with the suggestion by ) that it may be related to the high concentrations of exogenous neurotrophin applied in these studies using osmotic pumps.…”
Section: Effects Of Deafness Bdnf and Es On Sg Cell Soma Sizesupporting
confidence: 90%
See 3 more Smart Citations
“…However, the effects on soma area associated with neurotrophin administration are much greater than the cell size changes elicited with electrical stimulation. In fact, several previous studies in guinea pigs have shown that 4 weeks of intracochlear infusion of BDNF resulted in large increases in SG perikaryal size compared to deafened cochleae and cross-sectional areas that were even significantly larger than in normal controls (Agterberg et al 2008;Glueckert et al 2008;McGuinness and Shepherd 2005;Shepherd et al 2005Shepherd et al , 2008. The mechanism(s) underlying this alteration are unclear, but we agree with the suggestion by ) that it may be related to the high concentrations of exogenous neurotrophin applied in these studies using osmotic pumps.…”
Section: Effects Of Deafness Bdnf and Es On Sg Cell Soma Sizesupporting
confidence: 90%
“…Profound deafness has been reported to result in reduction in the size of SG neuron perikarya in many previous studies and in various deaf animal models (Agterberg et al 2008(Agterberg et al , 2009Araki et al 1998;Elverland and Mair 1980;Glueckert et al 2008;Leake et al 1999Leake et al , 2007Leake et al , 2011; Leake and Hradek 1988;McGuinness and Shepherd 2005;Shepherd et al 2005;Wise et al 2005). Presumably, reduction in somatic size reflects reduced metabolic requirements of these neurons due to reduced spike activity after deafness (Hartmann et al 1984;Liberman and Kiang 1978;Shepherd and Javel 1997).…”
Section: Effects Of Deafness Bdnf and Es On Sg Cell Soma Sizementioning
confidence: 95%
See 2 more Smart Citations
“…This degeneration has been associated with discontinued neurotrophic support from the organ of Corti (Ernfors et al 1995;Fritzsch et al 1999;Zilberstein et al 2012). Administration of exogenous neurotrophic factors has prevented SGC degeneration in multiple animal models of SNHL (for a review, see Ramekers et al 2012); SGCs are larger and more numerous after neurotrophic treatment than in untreated controls (Ernfors et al 1996;Richardson et al 2005;Shepherd et al 2005;Glueckert et al 2008;Agterberg et al 2008Agterberg et al , 2009Leake et al 2011;van Loon et al 2013).…”
Section: Introductionmentioning
confidence: 99%